Inter-professional education in a child mental health-care context: children's nursing and clinical psychology students learning together. Issue 1 (3rd December 2020) - Cust, Fiona; Combes, Helen; Priest, Helena; Cust, Henry
Abstract : Purpose: Previous research has explored inter-professional education (IPE) in mental health contexts, for example, between mental health nurses and clinical psychologists (CPs). However, little research has explored IPE with children's nurses (CNs) and CPs, who often work together in a range of in-patient and community mental health settings. Indeed, a significant proportion of CNs' work involves identifying and responding to the mental health needs of children, young people and families; equally, CPs work directly into child teams, and their consultancy work requires awareness of other professional roles. However, knowledge and understanding of roles, and true collaborative working, appears to be limited. This study aimed to address these limitations. Design/methodology/approach: A project was designed to bring together these two groups in an educational context, to explore ways in which collaborative working may enable effective mental health-care delivery. A total of 17 children's nursing students and 15 clinical psychology trainees participated in a 3-day workshop, including experiential and clinical vignette work. Workshops were evaluated at three time points, using a questionnaire. Findings: The workshops were effective in improving knowledge, skills and understanding of roles. Teamwork and discussions were helpful in modifying attitudes and perceptions. However, "defensiveness" was an important theme, demonstrating somewhat fixed beliefs about roles in relation to child mental health care. Originality/value: Few studies have explored IPE in child mental health contexts, especially in the pre-qualification arena.